A behaviour based cellular automaton model for pedestrian counter flow. (10th November 2016) - Xue, Shuqi; Jia, Bin; Jiang, Rui
Abstract: This paper presents a behaviour based cellular automaton (CA) model for pedestrian counter flow. The behaviours of active slowing down and lane changing are considered to simulate the evolution of the pedestrian counter flow in a corridor with open boundaries. A concept of a dominant row is introduced to depict the pedestrian's lane changing behaviour. The velocity profile has been investigated and two separation times have been studied, which quantify the evolution process of the lane formation. The simulation shows that steady separate lanes can form even in dense conditions. Therefore, the gridlock formation has been remarkably suppressed.